Hydrolysis and acidification of agricultural waste in a non-airtight system: Effect of solid content, temperature, and mixing mode. (January 2017) - Yu, Jiadong; Zhao, Yubin; Zhang, Huan; Hua, Binbin; Yuan, Xufeng; Zhu, Wanbin; Wang, Xiaofen; Cui, Zongjun
Highlights: We tested hydrolysis and acidification of rice straw and cow dung waste. Tests were performed in a non-airtight acidogenic system. High solid content hydrolysate (sCOD) reached 23, 280 mg/L on day 2. Temperature and mixing mode had minor effects during pretreatment. Solid content was the leading factor that affected organic acid production. Abstract: A two-phase digestion system for treating agricultural waste is beneficial for methane production. This study explored the effect of solid content, temperature, and mixing mode on the process of hydrolysis and acidification using rice straw and cow dung launched in non-airtight acidogenic system. The results showed that the substrate could be hydrolyzed efficiently in the initial stage, the hydrolysis coefficient ( k ) of maximum cellulose and hemicellulose can be increased by 217.9% and 290.5%, respectively, compared with those of middle and last stages. High solid content played a leading role in promoting hydrolysis, resulted in hydrolysate content (sCOD) that was significantly higher than in treatments with low solid content ( P  < 0.01), and led to organic acids accumulation up to 5.8 and 6.7 g/L at mesophilic and thermophilic temperatures. Thermophilic temperature stimulated the hydrolysis and acidification of low solid content ( P  < 0.05), and improved organic acid accumulation of high solid content only during the middle stage ( P  < 0.01). Mixing mode was not a major factor, but increasing the mixing time was necessary for organic acid accumulation during the last stage ( P  < 0.05). In addition, the study comprehensively analyzed a series of corresponding relationships among each operating parameter during the whole treatment process using canonical correspondence analysis.